Game Changer. - Marani, Matthew (Architectural Record, 2025)
The article discusses how architectural firms are increasingly utilizing video game engines, specifically Unreal Engine and Unity, to enhance project visualization and management. These engines allow architects to create interactive digital environments that facilitate better engagement with clients and stakeholders, streamline data visualization, and improve collaboration among project teams. Notable examples include the global firm Populous using Unreal Engine for the Kai Tak Sports Park in Hong Kong, and Revizto employing Unity to aggregate data for construction projects. The integration of these technologies is seen as a transformative step in the architectural profession, promising new methods of design and project execution.